Post-translational and Post-transcriptional Modifications of Pregnane X Receptor (PXR) in Regulation of the Cytochrome P450 Superfamily - Smutny, Tomas; Mani, Sridhar; Pavek, Petr (Current Drug Metabolism, 2013)
Pregnane X receptor (PXR) is a member of the nuclear receptor (NR) superfamily of ligand-activated transcription factors and is activated by a huge variety of endobiotics and xenobiotics, including many clinical drugs. PXR plays key roles not only as a xenosensor in the regulation of both major phase I and II drug metabolism and transporters but also as a physiological sensor in the modulation of bile acid and cholesterol metabolism, glucose and lipid metabolism, and bone and endocrine homeostasis. Post-translational modifications such as phosphorylation have been shown to modulate the activity of many NRs, including PXR, and constitute an important mechanism for crosstalk between signaling pathways and regulation of genes involved in both xenobiotic and endobiotic metabolism. In addition, microRNAs have recently been shown to constitute another level of PXR activity regulation. The objective of this review is to comprehensively summarize current understanding of post-transcriptional and post-translational modifications of PXR in regulation of xenobiotic-metabolizing cytochrome P450 (CYP) genes, mainly in hepatic tissue. We also discuss the importance of PXR in crosstalk with cell signaling pathways, which at the level of transcription modify expression of genes associated with some physiological and pathological stages in the organs. Finally, we indicate that these PXR modifications may have important impacts on CYP-mediated biotransformation of some clinically used drugs.
Keywords: PXR